Transformasi Kebijakan Ketenagakerjaan Menuju Indonesia Emas 2045: Pemanfaatan Machine Learning dalam Analisis Risiko Pengangguran - Rokhmawati, Anita; Aziz, Maulana Zulfikar (Politeknik Statistika STIS, 2024)
Indonesia is undergoing a positive development, marked by an increase in the productive population and economic capacity over the past two decades. With the vision of